Analysis of the Business Inequalities Stimulated by the Fourth Industrial Revolution Between Corporates and Small and Micro Enterprises in South Africa - Selelo , M.E.; Khwela, M.N. (Technium Social Sciences Journal, 2022)
Most of the authors have discussed how technology could enhance the effectiveness and efficiency of the production in various businesses. Yet, there is still a gap in literature, and little has been researched about the business inequalities which are fuelled by the Fourth Industrial Revolution (4IR) between Small and Micro Enterprises (SMEs) and corporates. The aim of this paper is to theoretically analyse the business inequalities instigated by the 4IR between corporates and SMEs. The paper argues that the 4IR is advocated by the corporates to increase their production because they are well-resourced and is a disadvantage to the SMEs due to their poor resources. The inadequate analysis of the business inequalities due to the inception of the 4IR provides a vacuum for further conceptual investigation of the phenomenon. The paper used literature-based methodology to analyze the business inequalities brought by the 4IR between corporates and SMEs. This methodology provided an extensive conceptual review of the literature regarding the subject under investigation. This paper reveals that the critical factor of production in corporates appears to be technology which increases production. In that, the 4IR is beneficial to the corporates and a disadvantage to the SMEs. Therefore, the literature indicated that there is an inevitable huge inequality between corporates and SMEs. The paper concludes that there are great business inequalities between corporates and SMEs brought by the 4IR. Thus, the paper recommends the support structures/organizations to assist the SMEs to respond to the growing technology and attempt to close the business inequalities.